Mechanistic insights into the C–H activation of methane mediated by the unsupported and silica-supported VO2OH and CrOOH: a DFT study. Issue 19 (17th March 2021) - Zhao, Shidong; Ma, Lishuang; Xi, Yanyan; Shang, Hongyan; Lin, Xufeng
Abstract : The support effect of silica was studied with DFT for the C–H bond activation of methane on a V(v ) or a Cr(iii ) site. Both of the PCET and HAT mechanisms were computationally characterized. Abstract : The direct activation and conversion of methane has been a topic of interest in both academia and industry for several decades. Deep understanding of the corresponding mechanism and reactivity mediated by diverse catalytic clusters, as well as the supporting materials, is still highly desired. In this work, the regulation mechanism of C–H bond activation of methane, mediated by the closed-shell VO2 OH, the open-shell CrOOH, and their silica supported clusters, has been investigated by density functional theory (DFT) calculations. The hydrogen-atom transfer (HAT) reaction towards methane C–H bond activation is more feasible when mediated by the unsupported/silica-supported CrOOH clusters versus the VO2 OH clusters, due to the intrinsic spin density located on the terminal Ot atom. The proton-coupled electron transfer (PCET) pathways are regulated by both the nucleophilicity of the Ot site and the electrophilicity of the metal center, which show no obvious difference in energy consumption among the four reactions examined. Moreover, the introduction of a silica support can lead to subtle influences on the intermolecular interaction between the CH4 molecule and the catalyst cluster, as well as the thermodynamics of the methane C–H activation.